NonCropShare coordination game - Bell, Andrew; Zhang, Wei; Bianchi, Felix; van der Werf, Wopke (International Food Policy Research Institute, 2013)
NonCropShare is an experimental field game, played by four players, that investigates how choices to maintain non-crop habitat or employ pesticides shift in response to changes in incentives. It is a form of coordination game. NonCropShare is currently being employed in Cambodia, Vietnam, and China to evaluate what kinds of conditions lead farmers to move away from intensive pesticide use. The current version of the NonCropShare program can be used only with NetLogo5. All game outputs are saved in a .csv format. This version of NonCropShare is intended to be used on a set of Windows-8 tablets, linked across a wireless network. The program currently features two interfaces: the Master and the Enumerator. In the "Master" version, all game parameters are adjustable from the NetLogo interface, but users should read the NonCropShare Info tab carefully to understand the role of each setting. The "Enumerator" version provides an example of a game interface used in experimental settings, with a set of easy-to-follow instructions for an enumeration team and few moving parts on the interface. Current language supported in NonCropShare are English, Chinese, Vietnamese, and Khmer.